(untitled) (Japan, 1998)
Field guide to important commercial marine fishes of the South China sea area is intended for easy use while, at the same, being comprehensive reference to serve various sectors such as fihery management, students, trademen as well as field officers and scinetists.
Keywords: Cá biển,Marine fishes,Fisheries